Several major herb pairs containing Coptidis rhizoma: a review of key traditional uses, constituents and compatibility effects - Li, Shi-Yu; Xu, Ding-Qiao; Chen, Yan-Yan; Fu, Rui-Jia; Tang, Yu-Ping (Frontiers in Pharmacology, 2024)
Herb compatibility is the soul of traditional Chinese Medicine prescriptions. Coptidis rhizoma (CR) (Coptis chinensis Franch., Coptis deltoidea C.Y.Cheng et Hsiao, or Coptis teeta Wall.; family Ranunculaceae), is a well-known herb. The bitter and cold nature of CR can irritate the spleen and stomach, and certain ingredients in CR may trigger allergic reactions. Herb combinations can help alleviate the side effects caused by CR. Through data analysis and literature research, there are many herbs combined with CR have a high frequency, but only a few are currently used as formulae in clinical practice. The results showed that these six herb pairs are usually widely studied or used as prescriptions in the clinic. This paper describes the six herb pairs from the key traditional uses, changes in bioactive constituents, and compatibility effects, especially with Euodiae fructus (family Rutaceae), Scutellariae radix (family Lamiaceae), Magnoliae Officinalis cortex (family Magnoliaceae), Glycyrrhizae radix et rhizoma (family Fabaceae), Ginseng radix et rhizoma (family Araliaceae), and Aucklandiae radix (family Asteraceae), and found that herbs are more effective when used in combination. Therefore, it is feasible to establish some methods to study herb pairs comprehensively from different perspectives. This paper aims to provide the latest and most comprehensive information on the six herb pairs and summarize the pattern of CR compatibility effects. It aims to attract more attention, and further experimental studies will be conducted to investigate and evaluate the effects of herb pairs containing CR. These data can also provide valuable references for researchers and also provide more possibilities for future applications in clinical practice and new drug development.